Reductions in Whole-body Ownership in Borderline Personality Disorder – A Phenomenological Manifestation of Dissociation. Issue 2 (14th March 2020) - Löffler, Annette; Kleindienst, Nikolaus; Cackowski, Sylvia; Schmidinger, Ilinca; Bekrater-Bodmann, Robin
ABSTRACT: Body ownership, i.e., the certainty that own body parts belongs to oneself, is a fundamental feature of self-consciousness. Patients with borderline personality disorder (BPD) often show symptoms of dissociation, describing a state of detachment from reality including their own body. However, up to now, there is no study that a) quantifies body ownership experiences in BPD, b) compares these experiences between the current and the remitted state of the disorder, and c) relates this kind of experience specifically to dissociation. In the present study, we assessed ownership for 25 body areas in current BPD patients (cBPD) and compared their ratings with those of remitted BPD patients (rBPD) and healthy controls (HC). We further related body ownership to dissociation and other relevant BPD markers on body area and subject level by applying multi-level analyses in the cBPD group. We found significantly reduced body ownership experiences in cBPD compared to HC, while there were no significant differences between these groups and rBPD. In cBPD, reduced body ownership was significantly related to dissociation when controlled for other BPD core features. Reduced body ownership might thus constitute a relevant marker for dissociation in current BPD which could further represent a target for therapeutic approaches.